Meningkatkan Motivasi dan Hasil Belajar Tematik Peserta Didik dengan Mengoptimalkan Penerapan Model Discovery Learning di SD Negeri 3 Cakranegara - Mahartati, I Gusti (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
This study aims to discover the effectiveness of the application of the scientific approach of Discovery Learning model in an effort to improve the motivation and learning outcomes of first grade students of PPKn lesson at SD Negeri 3 Cakranegara. The benefits of this research are to encourage learners to develop group learning skills (cognitive) and to socialize with friends in the actual learning process in the classroom. For teachers, it is to improve the development of approaches and models of learning with the application of scientific Discovery learning model in group work (cooperative). This research was conducted in two cycles, and each cycle activity consisted of planning, action, observation and reflection. The final result of action in cycle II showed that the results of teacher observation at the second meeting got the average score (4.29) and the result of the observation of the participants in the second meeting reached the average score (4.13). The impact of the increase in learning motivation was the increase of Learners learning achievement reached the average value (81,43), meaning that indicator of success (>4.0) and result of learning (>75,00) had been exceeded. Because indicator the success has been proven that the research is successful and stopped in cycle II.